Determination of agricultural infrastructural suitability in aspirational districts: A case study of Bundelkhand - JAIN, RAJNI; CHAND, PREM; AGARWAL, PRIYANKA; RAO, SULAKSHANA; PAL, SURESH (The Indian Journal of Agricultural Sciences, 2021)
Agricultural infrastructure has the potential to transform subsistence farming into commercial and dynamic farming system. Adequate markets, roads, irrigation, extension services, credit facilities, storage etc. facilitate lowering of farming costs and increase in farm income. The study, carried out during 2017-20 at ICAR-NIAP, presents methodology for measuring adequacy status of rural infrastructure and its categorisation into five classes using a case study of Bundelkhand region.The results show that there is ample scope for agricultural productivity enhancement in Bundelkhand by focussing on agricultural markets, credit institutions, roads, agricultural extension and storage infrastructure.The proposed methodology can be replicated for other regions, states and districts.